# Solve By Factoring And Using The Principle Of Zero Products. Show Work (x + 6)(x - 1) = 18 Can Some One Show Me The Steps I Am Lost At This One?

You need to multiply out the left side, subtract 18, then factor the result.

(x+6)(x-1) = 18

x^2 - x + 6x - 6 = 18 (multiply out the left side. You can use the FOIL method, if you are comfortable with that. Otherwise, just make use of the distributive property.)

x^2 + 5x - 24 = 0 (subtract 18 from both sides)

x^2 + 8x - 3x - 24 = 0 (we need factors of 24 whose difference is 5. 3 and 8 will do.)

x(x+8) - 3(x+8) = 0 (factor the first two terms and the last two terms)

(x+6)(x-1) = 18

x^2 - x + 6x - 6 = 18 (multiply out the left side. You can use the FOIL method, if you are comfortable with that. Otherwise, just make use of the distributive property.)

x^2 + 5x - 24 = 0 (subtract 18 from both sides)

x^2 + 8x - 3x - 24 = 0 (we need factors of 24 whose difference is 5. 3 and 8 will do.)

x(x+8) - 3(x+8) = 0 (factor the first two terms and the last two terms)

**(x-3)(x+8) = 0**(factor out the common factor from the above result)**The solution to this is the set of values for x that will make these factors zero. They are****x = 3, x = -8.**